Pengaruh Pelatihan Goal Setting Dalam Mengatasi Academic Boredom di Remaja Sidodadi Surabaya - Sheren Reggyna Herawan; Nabila Aurelia Rizqulah Sugijanto; Audrey Vivian Chandra; Sherly Yuriko Kato; Emre Omar Khaled; Livia Yuliawati; Tifani Meilianawati; Putri Ayu Puspieta; Mopheta Audiola Dorkas (Universitas Ciputra Surabaya, 2022)
During the pandemic, online learning led to the emergence of academic boredom due to the absence of face-to-face meetings. The existence of this boredom can reduce students' academic achievement, and can cause confusion in life purpose since they do not understand their goals. This study aims to determine the effect of goal setting training on academic boredom. The researcher used a purposive sampling technique with 10 participants aged 12-16 years in the